2017
DOI: 10.1515/eko-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Methods of trees evaluation with the site-specific effect for microclimate in urban environment: the case of study Nitra (Slovakia)

Abstract: Klein J., Rózová Z.: Methods of trees evaluation with the site-specific effect for microclimate in urban environment: the case of study Nitra (Slovakia). Ekológia (Bratislava), Vol. 36, No. 1, p. 40-51, 2017. Microclimatic factors in selected vegetation structures have been monitored in a compact historical built-up layout in the Nitra municipality. We have observed relationship between microclimatic factors (air temperature, relative air humidity and surface temperature) and microclimatic environment indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The study in the city of Poznan, Poland presented that coniferous canopy contributes less to the reduction of surface temperature than deciduous forest, where the reason for this is lower albedo of coniferous trees (Majkowska et al, 2017). When evaluating surface temperature and relative air humidity in Nitra, Slovakia, it was found that the cooling effect is dependent on the canopy shape and tree crown cover and reaches from 0.55 to 1.83 o C as compared to a street without green elements (Klein, Rózová, 2017). From the category of support services, many publications emphasize the development and maintenance of biodiversity, for example, amphibians, birds, mammals, insects (Goddard et al, 2010;Niemelä, 2014).…”
Section: Urban Green Areas and Woody Plant Composition: Dwelling Spac...mentioning
confidence: 99%
“…The study in the city of Poznan, Poland presented that coniferous canopy contributes less to the reduction of surface temperature than deciduous forest, where the reason for this is lower albedo of coniferous trees (Majkowska et al, 2017). When evaluating surface temperature and relative air humidity in Nitra, Slovakia, it was found that the cooling effect is dependent on the canopy shape and tree crown cover and reaches from 0.55 to 1.83 o C as compared to a street without green elements (Klein, Rózová, 2017). From the category of support services, many publications emphasize the development and maintenance of biodiversity, for example, amphibians, birds, mammals, insects (Goddard et al, 2010;Niemelä, 2014).…”
Section: Urban Green Areas and Woody Plant Composition: Dwelling Spac...mentioning
confidence: 99%
“…Concerning the green areas greater than 10 hectares, the positive correlation and a good cooling effect was shown (Yu et al, 2018). When evaluating the microclimate factors of the urban vegetation (surface temperature and air humidity) in Nitra town, it was found that the cooling effect is dependent on the canopy shape and a tree crown cover and reaches a differential value of 0.55 °C to 1.83 °C, compared to the streets without any green areas (Klein and Rózová, 2017). The aim of the contribution is to present the microclimatic measurements in Nitra town territory with an emphasis on the differences in the compared areas of the urban green spaces and the open areas without greenery.…”
mentioning
confidence: 95%